Hubungan Pengetahuan dengan Perilaku Diet Hipertensi: Relationship between Knowledge and Hypertension Diet Behavior - Fitriani; Titi Iswanti Afelya; Syahrani Hikmatullah Syam; Dg Mangemba (Lentora Nursing Journal, 2023)
Introduction: Behavior is an important component of individual success in improving their health status. Dietary behavior for hypertensive patients is one of the efforts recommended by health workers to stabilize blood pressure. Knowledge is very influential on hypertensive patients in carrying out dietary compliance. Objective: To determine the relationship between knowledge and hypertension diet behavior. Methods: Descriptive research type, correlation method with cross sectional approach. The study population was hypertensive patients with a total sample of 83 selected by purposive sampling technique. Data collection using a questionnaire. Results: The results showed that there was a relationship between knowledge and hypertension diet behavior with a p-value of 0.006. Conclusion: There is a relationship between knowledge and hypertension diet behavior. The research suggestion is that further research be carried out to discuss hypertensive diet behavior in more depth with observation.